A study of Basic Financial Knowledge among women working in service sector of Delhi - Rawat, Anviti (International Journal of Membrane Science and Technology, 2023)
The study titled Assessment of Basic Financial Knowledge among Women in the Service Sector examines the financial literacy of 390 women in Delhi's service sector. Employing a descriptive survey method and snowball sampling, the research employs a self-constructed questionnaire, the "Financial Literacy Tool for Working Women," divided into demographic information (Section A) and financial competence assessment (Section B). Results indicate a moderate level of basic financial knowledge among respondents, revealing gaps in areas such as risk and return concepts, types of bank accounts, portfolio management, and time value of money. The study categorizes respondents into medium (72.8%), high (13.6%), and low (13.6%) basic financial knowledge levels. Despite an average score of 13.3 out of 19, highlighting a good understanding of financial basics, the research underscores the need for targeted interventions to address specific knowledge gaps. Findings align with previous studies, emphasizing the gap between financial education and practical decision-making. In conclusion, the study provides insights into the financial literacy of women in Delhi's service sector, recommends strategies for improvement, and emphasizes the importance of tailored interventions to enhance financial confidence.